Misconceptions about the concept of photosynthesis among grade 12 students using the image analysis method - Evi Aprianti; Ari Sunandar; Anandita Eka Setiadi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Understanding the photosynthesis concepts is challenging due to its abstract nature, often leading to student misconceptions. This study aims to identify and analyze misconceptions among science and social studies students using the image analysis method. A total of 78 students (32 science, 46 social studies) participated, selected through a nonprobability sampling technique. Data were collected via image-based tests and interviews, with misconceptions categorized using established image analysis criteria. Findings indicate that misconceptions were more prevalent among social studies students (63.04%) than science students (59.38%). However, conceptual variation was greater among science students. Additionally, 13.04% of social studies students exhibited a complete lack of understanding, whereas all science students demonstrated some level of conceptual awareness. Misconceptions primarily revolved around the location, materials, and products of photosynthesis. Science students mistakenly believed chlorophyll to be the organelle where photosynthesis occurs, while social studies students commonly misidentified the inputs and outputs of the process. These misconceptions stemmed from differences in curriculum structure, instructional time, cognitive abilities, and prior knowledge. Future research should focus on longitudinal intervention strategies and comparative pedagogical studies to improve conceptual understanding of abstract biological processes.